Peningkatan Kemampuan Menulis Karya Ilmiah Melalui Project-based Learning - Krisnawati, Vera; Nia Ulfa Martha (Multiverse: Open Multidisciplinary Journal, 2023)
This article aims to describe improving the quality of the process of learning to write scientific papers using Project-based Learning and to describe improving the ability to write scientific papers using Project-based Learning. This classroom action research consists of action planning, action implementation, observation, analysis and reflection. This research was carried out in two cycles by paying attention to completeness according to predetermined criteria. The results of this study indicate an increase in the quality of the process for two cycles in terms of activeness, attention, and implementation. Aspects of student activity are reviewed when students conduct questions and answers to lecturers and other students, are involved in solving problems, carrying out projects, and carrying out group discussions according to instructions in the learning process. Student attention is reviewed when paying attention to the explanation delivered by the lecturer. Furthermore, student implementation is reviewed when understanding and following the instructions given, participating in completing the project, completing the project on time, utilizing all learning resources, and mastering the material presented by the lecturer. Student activity, student attention, and student achievement have increased. The increase in the ability to write students' scientific papers can be proven from the increase in grades in cycle I and cycle II. Thus, the application of Project-based Learning can improve the quality of the process and the ability to write scientific work of students.